1993
DOI: 10.1130/0091-7613(1993)021<0797:docdnt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of channel deposits near the Cretaceous-Tertiary boundary in northeastern Mexico: Catastrophic or "normal" sedimentary deposits?

Abstract: science. This file may not be posted to any Web site, but authors may post the abstracts only of their articles unlimited copies of items in GSA's journals for noncommercial use in classrooms to further education and use a single figure, a single table, and/or a brief paragraph of text in subsequent works and to make employment. Individual scientists are hereby granted permission, without fees or further requests to GSA, to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 12 publications
2
67
0
1
Order By: Relevance
“…Environmental conditions before, during and after the Chicxulub impact event are still controversial despite analyses of numerous Cretaceous-Tertiary (K/T) boundary sections throughout Central America and the Caribbean by various research groups (Smit et al, , 1996Bohor and Betterton, 1993;Smit, 1999;Bohor, 1996;Stinnesbeck et al, 1993;Stinnesbeck and Keller, l996;Claeys et al, 2002;Keller et al, 2002aKeller et al, ,c, 2003Keller et al, , 2004a. Aspects central to this controversy concern the exact stratigraphic position of the K/T boundary, the age and depositional nature of impact spherules, and the nature and emplacement of marls and siliciclastic sediments that characteristically separate the K/T boundary from the underlying impact spherules.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions before, during and after the Chicxulub impact event are still controversial despite analyses of numerous Cretaceous-Tertiary (K/T) boundary sections throughout Central America and the Caribbean by various research groups (Smit et al, , 1996Bohor and Betterton, 1993;Smit, 1999;Bohor, 1996;Stinnesbeck et al, 1993;Stinnesbeck and Keller, l996;Claeys et al, 2002;Keller et al, 2002aKeller et al, ,c, 2003Keller et al, , 2004a. Aspects central to this controversy concern the exact stratigraphic position of the K/T boundary, the age and depositional nature of impact spherules, and the nature and emplacement of marls and siliciclastic sediments that characteristically separate the K/T boundary from the underlying impact spherules.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that, despite all the data favoring an impact origin of the Haiti glasses, a few authors have suggested that the glasses are of volcanic origin (e.g., Stinnesbeck et al 1993) or that there is no evidence at all for impact deposits at Beloc (e.g., Jéhanno et al 1992). However, there is abundant evidence on the impact origin of these glass spherules based on water content (Koeberl 1992) and geochemistry (Koeberl and Sigurdsson 1992;Koeberl 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These observations made a convincing case for Chicxulub as the long-sought K-T boundary impact crater and cause for the end-Cretaceous mass extinction. But doubts persisted regarding the precise age and size of the impact crater (2)(3)(4)9), the origin of the so-called megatsunami deposits (5,(10)(11)(12), and the nature of the mass extinction (13,14). To resolve these issues, the International Continental Scientific Drilling Program (ICDP) supported the drilling of a new core within the Chicxulub crater (Yaxcopoil-1 drilled between December 2001 and February 2002) with the stated objectives to determine the precise age of the crater and its link to the global K-T boundary layer, to unravel Chicxulub's role in the K-T mass extinction, and to study the cratering event and size of the impact crater (15).…”
mentioning
confidence: 99%